(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
One of the most serious medical conditions is tuberculosis (TB). In Mycobacterium tuberculosis (Mtb), the NADH-quinone oxidoreductase subunit C (NuoC) protein is a member of the NADH dehydrogenase family and is essential to the electron transport chain, ATP generation, and energy production. One possible pharmacological target for finding inhibitors is the Nuoc protein. Computational approaches are used to identify the 3D structural characteristics of the Nuoc protein, and several validation methods are used to verify the results. Using several ligand databases, virtual screening tests surrounding the active site were carried out to find drug-like molecules. The study found that the amino acid residues that are important in drug-target interactions are ARG98, ARG75 (basic), ASP99, ASP189, ASP98 (acidic), LEU101, LEU194 (nonpolar neutral), THR180 (polar neutral), GLU177 (polar neutral), TYR181 (polar neutral), PRO102, PRO192 (nonpolar neutral), and HIS191 (basic). The findings demonstrate the ligand molecules’ drug-like ability to inhibit NuoC proteins. The structural data may be used to develop novel therapeutic scaffolds for the treatment of tuberculosis (TB), in conjunction with information on the active site and the chosen ligand molecules.